THF-enabled PtBr2-catalyzed desymmetric hydrogenative [3 + 2] cycloaddition of 2-alkynylbenzaldehyde-tethered cyclohexadienones. Issue 13 (27th May 2022) - Hu, Rui; Chen, Jichao; Wang, Zeliang; Shang, Dandan; Yu, Lei; Chan, Philip Wai Hong; Rao, Weidong
Abstract : A rare instance in platinum catalysis of an in situ formed Pt-bound benzopyrylium species that undergoes [3 + 2] cycloaddition with an electron-deficient alkene tether followed by THF-enabled hydrogenation. Abstract : A THF-enabled PtBr2 -catalyzed desymmetric hydrogenative [3 + 2] cycloaddition of 2-alkynylbenzaldehyde-tethered cyclohexadienones has been developed. The protocol provides a highly functionalized 6-7-6 polycyclic skeleton with four contiguous stereocenters in good to excellent yields of up to 97% yield and with exclusive exo -selectivity. The suggested cascade reaction pathway delineates a rare instance in platinum catalysis of the involvement of an in situ formed Pt-bound benzopyrylium species that participates in a Huisgen-type [3 + 2] cycloaddition with an electron-deficient alkene tether in the highly reactive organometallic intermediate. It also offers the first example of a metallocarbene species generated in this manner which undergoes hydrogenation with THF as the hydride transfer source. The synthetic utility of the catalytic method was exemplified by the late-stage stereoselective modification of the steroids estrone and estradiol under mild reaction conditions.